Re-introdução do dourado (salminus brasiliensis) nas cabeceiras do Rio dos Sinos: o efeito da densidade sobre a dispersão - Leal, Mateus Evangelista (Universidade do Vale do Rio do Sinos, 2009)
The main goal of restocking programs is the natural stocks restoration. The Sinos River are listed as one of the eight most polluted rivers in the country, and now, revitalization programs are being developed to recover the damages. The dorado (Salminus brasiliensis) is an endangered species in Rio Grande do Sul, widely studied in the basin. The objectives of that study is reintroduce dorado juvenile in headwaters of the Sinos River and test the effect of density on displacement. In the assessment was used radiotelemetry, where nanotags were introduced in 25 dorado, sub-sample of 200 fish released. The fish were released at two events, one in a lower density (0.017 peixes/m-2) and another at higher density (0.040 peixes/m-2). Were screened for 120 days. The site fidelity was 68%, 20% inefficiency and emigration 12%. The peak of displacement occurred in the early days of the introduction. The individual’s movements in the first event are less than those of the second. The reintroduction program results were a
Keywords: densidade; dispersão; repovoamento; salminus brasiliensis; dourado; density; displacement; restocking; salminus brasiliensis; dorado; Ciências Biológicas